A Study of Effectiveness of Teaching Method on Achievement of Standard 7th Students for Topic Volume in Mathematics Subject - Jogani, Chintan Gautambhai; Dodiya, Malabhai B. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Mathematics, as a foundational subject, plays a critical role in developing logical reasoning and problem-solving skills. However, students often struggle with abstract concepts such as “Volume” due to lack of concrete experiences and effective teaching strategies. This study aimed to evaluate the effectiveness of an activity-based teaching method compared to traditional lecture-based instruction in improving the achievement of Standard 7 students on the topic of Volume in mathematics. A quasi-experimental pre-test–post-test control group design was employed. The sample consisted of 60 students from two sections of Standard 7 in a government-aided school in Gujarat, with 30 students in the experimental group and 30 in the control group. The experimental group was taught using an activity-based method involving hands-on models, measurement tasks, and group work, while the control group received conventional chalk-and-talk instruction. Achievement was measured using a researcher-developed Mathematics Achievement Test (MAT) validated by experts (CVI = 0.93, reliability = 0.88). Data analysis using an independent samples t-test revealed a statistically significant improvement in the experimental group’s post-test scores compared to the control group. The findings suggest that activity-based teaching is more effective for enhancing understanding of Volume concepts. The study recommends wider adoption of such methods in mathematics classrooms.